The Effect of Flipped Classroom Learning Assisted by Computer Simulation on Students' Comprehension of Simple Harmonic Motion - Theo Jhoni Hartanto; Suhartono; Budi Santoso; Zen Frianto (Jurnal Penelitian Pendidikan IPA, 2024)
Innovation in science learning is highly recommended by various studies and education experts. Through this learning innovation, teachers create learning that facilitates students' curiosity by getting them involved in learning, which ultimately helps them understand science in depth. However, the current trend is that science classes "fail" to create innovative learning that can foster students' interest in science, so that many students do not understand science well. This research aims to determine the impact of flipped classroom learning on simple harmonic motion material assisted by computer simulations on students' conceptual understanding. A pre-experiment with a one-group pretest-posttest design was used in this research. Class X of the MIPA program was chosen as the experimental object in this research, and 30 students were used as samples. The test given is a multiple-choice test with explanations. The results showed that the average post-test score was better than the pre-test. The N-gain score is 0.79, which indicates that there is an increase in students' understanding in the high category. This shows that flipped classroom learning assisted by computer simulations can increase students' understanding of the concept of simple harmonic motion. By implementing computer simulation activities that are integrated into flipped classroom learning, learning alternatives can be enriched to help students understand science.